Studies on analgesic and anti inflammatory effect of the ethanolic leaf extract of momordica charantia L in animal model - Showkat, Mir; Ullah, M.; Ahmed, Nazim Uddin; Islam, Saiful; Sarker, Md. Zaidul Islam; Absar, Nurul (Vivek Daniel, Ed.& Pub, 2011)
Momordica charantia Linn, commonly known as bitter gourd is used as a vegetable in various coun-tries in the world. The extracts of the bitter gourd plants, fruit and seed have been reported to use as a traditional medicine most commonly as anti-diabetic agents. We have studied the Momordica charantia leaves extract to evaluate the phytochemical constituents as well as its pharmacological action. The ethanolic extract of the leaves showed the presence of alkaloids, flavonoid, glycoside, steroids ,carbohydrates ,protein and amino acid. The present study was carried out using acetic acid-induced writhing and tail-immersion tests in mice, and caragennan induced paw edema in rat. The ethanolic extracts of leaves showed both analgesic and anti inflammatory effect at 500 mg/kg, p.o. These effect was found to be 57.12 % , 43.1% and 58.69% respectively in compare to control animals . The ethanol extract of Momordica charantia leaves was effective in both non-narcotic and narcotic models of nociception, suggesting its possible action via peripheral and cen-tral mechanism .The activity may be attributed to the phytoconstituents viz flavonoids ,steroids present in the extract.